Relationship of white matter lesion severity with early and late outcomes after mechanical thrombectomy for large vessel stroke. (15th May 2020) - Albo, Zimbul; Marino, Jose; Nagy, Muhammad; Jayaraman, Dilip K; Azeem, Muhammad U; Puri, Ajit S; Henninger, Nils
Abstract : Background: White matter lesions (WML) are associated with poor outcome after mechanical thrombectomy (MT) for large vessel stroke; the reasons are uncertain. To elucidate this issue we sought to determine the association of WML with multiple early and late outcome measures after MT. Methods: We retrospectively analyzed 181 MT patients prospectively included in our local stroke registry (January 2012 to November 2016). Using multiple regression modeling, we assessed whether WML was independently associated with early outcomes (successful recanalization, degree of National Institutes of Health Stroke Scale (NIHSS) improvement, hemorrhagic transformation, duration of hospitalization) as well as an unfavorable 90-day modified Rankin Scale score (mRS) (≥3) and 90-day survival. Explorative analyses examined the association with the 90-day home-time and 90-day risk for hospital readmission. Results: WML were not significantly associated with early outcome measure (P>0.05, each). Patients with moderate-to-severe WML more often had an unfavorable mRS (OR 2.93, 95% CI 1.04 to 8.33) and risk of death (HR 1.98, 95% CI 1.03 to 3.84) after adjustment for pertinent confounders. Patients with moderate-to-severe WML had a significantly shorter home-time (19±32 vs 47±38 days, P<0.001) and Kaplan–Meier analyses indicated a significantly greater risk for hospital readmission within 90 days (log rank P=0.045), with the most frequent reasons being recurrent stroke and transient ischemic attack. Conclusion: Our analyses suggest that poor outcomes among patients with moderate-to-severe WML were related to factors unrelated to procedural success and risk. WML should not be used to render treatment decisions in otherwise eligible patients. Aggressive monitoring of medical complications after MT could represent a viable strategy to improve outcome in affected patients.